Motility in Oscillatoria salina as affected by different factors - Gupta, S; Agrawal, S C (Folia microbiologica, 2006)
All 3-10-d-old Oscillatoria salina filaments glide with the speed of 323-330 microm/min (BG 11 medium, pH 7.5, 21 +/- 2 degrees C, continuous light intensity of approximately 30 micromol m(-2) s(-1)) in a culture chamber. However, a time bound progressive decrease in gliding speed and in percentage of gliding filaments occurred, depending upon the severity of different stress factors studied, viz. water stress (2-8% agarized media, liquid media with 0.2-1 mol/L NaCl, blot-dryness of filaments for > or = 5 min), temperature shock (5, 40 degrees C for > or = 5 min; 35 degrees C for > or = 15 min), darkness and low light intensity (2, 10 micromol m(-2) s(-1)), UV exposure (0.96-3.84 kJ/m2), pH extremes (< or = 6.5 and > or = 9.5), lack of all nutrients from liquid medium (double distilled water), presence of 'heavy' metals (1, 25 ppm Fe, Cu, Zn, Ni, Co, Hg) or organic substances in liquid medium (25, 250 ppm 2,4-D, captan, urea, DDT, thiourea). This feature of the alga (i.e. reduction in speed and percentage of gliding filaments depending upon severity of stress conditions) may thus be suggested to be used in assessing water quality.
Keywords: Organic Chemicals; Cyanobacteria; tma; Movement; sinice; pohyb; vysoká teplota; Hydrogen-Ion Concentration; osmotický tlak; Hot Temperature; Anti-Bacterial Agents; Ultraviolet Rays; Osmotic Pressure; Light; Darkness; těžké kovy; organické látky; světlo; antibakteriální látky; koncentrace vodíkových iontů; Metals, Heavy; ultrafialové záření